Slope Stability Analysis at JLS Lot 3 Blitar with Soil Nailing Reinforcement under Seismic Loading Using Finite Element Method - Siti Fauziah; Yerry Kahaditu Firmansyah; Bagas Aryaseta; Miguel Felix Wijaya (EPI International Journal of Engineering, 2025)
Slope stability in hilly areas with high seismic activity requires thorough geotechnical assessment to prevent potential failures that could endanger infrastructure and human safety. This study evaluates the effectiveness of soil nailing combined with shotcrete in reinforcing slopes under both static and seismic conditions at JLS Lot 3, Blitar. A two-dimensional finite element method (FEM) with plane strain modeling was applied to simulate slope behavior, including staged construction procedures and soil-structure interaction. Soil parameters were derived from bore log data, corrected for groundwater table and overburden effects, and used to define unit weight, cohesion, internal friction angle, modulus of elasticity, and Poisson’s ratio. The slope geometry was carefully modeled with attention to benching, slope angles, and shotcrete coverage. Surface loads representing construction, traffic, and pavement conditions were applied to the model to reflect realistic field scenarios. Results show that, without seismic loading, the reinforced slope reached a safety factor of 1.575, exceeding the minimum criterion of 1.50. When seismic loading was applied, the safety factor decreased to 1.106 but remained above the required 1.10 threshold, demonstrating that soil nailing with shotcrete effectively improves slope stability and controls deformation. The study emphasizes the importance of reinforcement design parameters, such as nail length, spacing, inclination angle, and shotcrete thickness, providing insights for optimizing slope reinforcement strategies under seismic conditions. The findings contribute to safer and more resilient slope design practices in earthquake-prone areas.